The Legal Power of the Constitutional Court Decisions Remains - Suandika, I Nyoman; Usfunan, Yohanes; Palguna, I Dewa Gede; Adiyaryani, Ni Nengah (International Journal Labs, 2023)
Issues relating to granting permanent legal force to decisions of the constitutional court immediately after they are pronounced in a plenary session open to the public are important to research for several reasons Firstly, it is very important for us to know the rationale for granting permanent legal force to decisions of the constitutional court given immediately after completion. pronounced in a public meeting open to the public. Second, understanding the permanent legal force of constitutional court decisions is also related to the question of why it is not possible to have legal efforts to correct constitutional court decisions if errors occur in terms of achieving legal certainty. Based on this, the question also arises as to whether the constitutional court's decision regarding this error will continue or not. Third, it is related to whether the legislator (positive legislator) can override the decision of the constitutional court. What is the rationale underlying the granting of permanent legal force to a Constitutional Court decision from the moment it is pronounced in a session open to the public? This research is normative legal research because there is a legal vacuum if the constitutional court's decision is contrary to the spirit of the 1945 Constitution. The importance of immediacy in granting permanent character to the constitutional court's decision, if viewed from the law in book aspect, is indeed the best choice. This is based on the following reasons. First, the Constitutional Court was formed to protect the purity of the Constitution with a more detailed interpretation. This interpretation will be used as a basis for resolving problems by certain authorities who are given direct authority by the Constitution. Therefore, it is appropriate that the interpretation is only carried out once, which is binding so that the decision must be placed at the first and final level where no effort can be made to cancel it. Second, apart from that, it must also be understood that the constitutional court as a constitutional court can resolve problems and provide legal certainty quickly by the principles of fast and simple justice.